Computed tomography–guided percutaneous transthoracic core needle biopsy for the diagnosis of mediastinal masses - Sukanta Kodali; Sourindra Nath Banerjee; Jaydip Deb; Pulak Kumar Jana (The Journal of Association of Chest Physicians)
Mediastinal masses encompass a wide spectrum of diseases; therefore, histopathological diagnosis is crucial for adequate surgical or medical treatments. Herein, we report six cases of mediastinal tumors that were definitively diagnosed by computed tomography (CT)-guided core needle biopsy. Case 1: A 35-year-old woman was found to have an anterior mediastinal mass on both a chest X-ray and a CT thorax. A CT-guided core needle biopsy of the mediastinal mass revealed type A thymoma. The patient underwent surgery and remained well 1 year of post-surgery. Case 2: A 47-year-old man was found to have a solid and cystic mass with areas of calcifications on a CT scan. A CT-guided core needle biopsy of the mediastinal mass revealed an immature teratoma. The patient is now under chemotherapy. Case 3: An 18-year-old boy was found to have a tumor in the anterior mediastinum on both a chest x-ray and CT scan. A CT-guided core needle biopsy of the mediastinal mass revealed a yolk sac tumor. The patient received only two cycles of chemotherapy and died. Case 4: A 26-year-old man was found to have a left anterior mediastinal mass with internal necrosis and calcification on a CT scan. A CT-guided core needle biopsy of the mediastinal mass revealed a malignant germ cell tumor. The patient is now under chemotherapy. Case 5: A 17-year-old boy was found to have an anterior mediastinal mass on both a chest X-ray and a CT scan. A CT-guided core needle biopsy of the mediastinal mass showed non-Hodgkin lymphoma. The patient received chemotherapy and remained well 6 months after the treatment. Case 6: An 8-year-old child was found to have an anterior mediastinal mass on a chest C-ray and a CT scan. A CT-guided core needle biopsy of the mediastinal mass revealed neuroblastoma. After six courses of chemotherapy the patient passed away. Percutaneous CT-guided core needle biopsy of mediastinal mass lesions is a safe, accurate, and cost-effective procedure.